2021
DOI: 10.1213/ane.0000000000005479
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obstructive Sleep Apnea With Difficult Intubation: Prospective Multicenter Observational Cohort Study

Abstract: BACKGROUND: Obstructive sleep apnea (OSA) has been found to be associated with difficult airway, although there is a paucity of prospective studies investigating thresholds of OSA severity with difficult airway outcomes. The aim of this study was to examine the association between OSA and difficult intubation or difficult mask ventilation. We also explored the utility of the Snoring, Tiredness, Observed apnea, high blood Pressure, Body mass index, Age, Neck circumference, and Gender (STOP-Bang) sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…A recent large prospective international cohort study by Seet et al on 869 patients with unrecognized OSA reported that moderate (defined as AHI 15 to 30 events/h) and severe OSA (defined as AHI > 30 events/h) were independently associated with DI. 40 Multivariable logistic regression analysis showed that the incidence of DI was 3-fold higher in moderate OSA [odds ratio (OR): 3.26, 95% confidence interval (CI): 1.37-8.38], and 4-fold higher in severe OSA (OR: 4.05, 95% CI: 1.51-11.36). In the same study, a comparable relationship was demonstrated in patients with higher STOP-Bang scores, where the incidence of DI was 3-fold in patients with STOP-Bang scores of 3-4 (OR: 3.01, 95% CI: 1.13-10.40, P = 0.046) and 4-fold in patients with scores of 5 to 8 (OR: 4.38, 95% CI: 1.46-16.36).…”
Section: Association Between Osa Patients and The Difficult Airwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large prospective international cohort study by Seet et al on 869 patients with unrecognized OSA reported that moderate (defined as AHI 15 to 30 events/h) and severe OSA (defined as AHI > 30 events/h) were independently associated with DI. 40 Multivariable logistic regression analysis showed that the incidence of DI was 3-fold higher in moderate OSA [odds ratio (OR): 3.26, 95% confidence interval (CI): 1.37-8.38], and 4-fold higher in severe OSA (OR: 4.05, 95% CI: 1.51-11.36). In the same study, a comparable relationship was demonstrated in patients with higher STOP-Bang scores, where the incidence of DI was 3-fold in patients with STOP-Bang scores of 3-4 (OR: 3.01, 95% CI: 1.13-10.40, P = 0.046) and 4-fold in patients with scores of 5 to 8 (OR: 4.38, 95% CI: 1.46-16.36).…”
Section: Association Between Osa Patients and The Difficult Airwaymentioning
confidence: 99%
“…7 One recent large prospective international cohort study demonstrated that moderate to severe OSA and STOP-Bang scores of ≥ 3 were independently associated with DI. 40 The Society of Anesthesia and Sleep Medicine recommends that patients with OSA and patients at risk of OSA should be considered at risk of DMV and/or DI. 7 Therefore, anesthesia providers should be vigilant, and adequate preparations should be made for these vulnerable patients to avoid adverse events.…”
Section: Association Between Osa Patients and The Difficult Airwaymentioning
confidence: 99%
“…28 Physical examination findings common in patients with OSA include obesity, increased fat deposition in the neck and pharynx, an enlarged tongue, enhanced tonsils, and a small upper airway diameter. 1,29 This can result in difficult mask ventilation and poor visualization of the vocal cords during direct or video laryngoscopy. This can predispose patients to perioperative airway trauma and laryngeal injury leading to edema, more rapid oxygen desaturation, and aspiration.…”
Section: Airway Managementmentioning
confidence: 99%
“…Patients with OSA and obesity can have more collapsible upper airways and reduced functional residual capacity (FRC) that predispose them to rapid desaturation, even after short periods of apnea or hypoventilation. [ 42 43 ] OSA has been found to be a risk factor for difficult tracheal intubation (DI)[ 43 ] and difficult mask ventilation (DMV). [ 12 44 45 46 47 ] Furthermore, the Fourth National Audit Project (NAP4), found that patients with obesity (BMI 30–35 kg/m 2 ) and morbid obesity (BMI >35 kg/m 2 ) had twice and four times as many serious airway complications as patients without obesity, respectively.…”
Section: Intraoperative Managementmentioning
confidence: 99%